Mirrors in Russian Decadent and Symbolist Prose: Valery Briusov and Dmitry Merezhkovsky - Kirsten Lodge (Studies in 20th & 21st Century Literature, 2010)
Examining mirror imagery in the prose works “In the Mirror” by Valery Briusov and The Resurrected Gods: Leonardo da Vinci by Dmitry Merezhkovsky, both published in 1902, this article situates the Russian Decadent and Symbolist associations of the mirror in the pan-European literary and philosophical context. The mirror constitutes the threshold of manifold oppositions, including life and art, life and death, and reality and dream or imagination. It is a realm of alternative reality, magical and seductive, as in Briusov’s story, or potentially both demonic and divine, as in Merezhkovsky’s novel. In accordance with the Romantic tradition as well as Decadent and Symbolist iconography, mirror imagery in these two works is inseparable from questions of the nature of art and the power of artistic creation.
Keywords: mirror; “In the Mirror”; Valery Briusov; The Resurrected Gods: Leonardo da Vinci; Dmitry Merezhkovsky; Russian Decadent; Symbolism; Mirror Symbolism; demonic; devine; Romantic tradition; Romanticism; nature of art; power of artistic creation